MULTINATIONAL WORKING CAPITAL MANAGEMENT CENTRALIZED CASH MANAGEMENT, OPTIMIZATION CASH FLOW, AND INVESTMENT OF EXCESS CASH: APPROACHES SYSTEMATIC LITERATURE REVIEW - Zulfikar Akbar; Malik Ibrahim; Fathullah Fathullah (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2024)
This study aims to analyze working capital management in multinational companies, focusing on centralized cash management, cash flow optimization, and excess cash investment. In the context of multinational companies, efficient cash management is essential to ensure adequate liquidity, reduce dependence on external financing, and increase profitability. Centralized cash management allows companies to consolidate all funds owned and optimize cash flow across various branches or subsidiaries.Meanwhile, cash flow optimization is carried out through efficient cash cycle management, by accelerating receipts and slowing debt payments. Excess cash investment, which consists of funds not used in operational activities, is an important source for companies to increase returns while maintaining sufficient liquidity. This study also explores the application of technology in cash management, such as the use of artificial intelligence (AI) and integrated cash management systems, which enable faster and more accurate decision making in cash flow management and excess cash investment. The results of the study indicate that good cash management can improve operational efficiency and strengthen the financial position of multinational companies, with a positive impact on long-term performance. Therefore, the right working capital management strategy is essential for multinational companies to survive and thrive in a dynamic global market.